GIANT 3RD-ORDER NONLINEAR SUSCEPTIBILITIES FOR INPLANE FAR-INFRARED EXCITATION OF SINGLE INAS QUANTUM-WELLS - Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Nguyen, C.; Kroemer, H. (Solid-State Electronics, 1994)
Third-order, free-carrier nonlinear susceptibilities, chi(3), have been measured between 19 and 23 cm-1 for three InAs/AlSb quantum wells with sheet densities between 2.5 x 10(12) cm-2 and 8 x 10(12) cm-2. We find that these wells are strongly nonlinear at far-infrared frequencies: odd harmonics ninth order have been observed at high incident intensities, and the peak value of chi(3) reaches approximately 1 esu. This is several orders of magnitude larger than previously reported values for chi(3) in bulk n-GaAs (10(-4) esu)[1] and in polyacetylene (10(-7) esu)[2]. The large magnitude of chi(3) is attributed to the high carrier density in the InAs wells, and to the strong non-parabolicity of the conduction band in InAs. However, the free-carrier chi(3) for bulk InAs predicts a density-dependence different from that observed, and the measured decrease in chi(3) with increasing intensity indicates non-perturbative response. We find that the anisotropy of chi(3) displays the expected 4-fold symmetry.